Learning and Learning Styles According to David Kolb - Kemhuy, Suksela (Educia Journal, 2023)
This article discusses about Learning and Learning Styles. Learning style is a combination of feelings and actions (feeling and doing), namely a learning style that interprets the experience through living it in a concrete way and transforms the experience into active experimentation. Student learning style can be defined as the cognitive, affective, and psychological characteristics of a student about how he understands something, interacts and responds to his learning environment, which is unique and relatively stable. In various literatures on learning and learning, we will come across a number of concepts about student learning styles, and one of them is learning styles as suggested by David Kolb, an education expert from the United States, who popularized the learning theory "Experiential Learning".